2006
DOI: 10.1002/elps.200500912
|View full text |Cite
|
Sign up to set email alerts
|

A complexomic study of Escherichia coli using two‐dimensional blue native/SDS polyacrylamide gel electrophoresis

Abstract: Study of the complexome - all the protein complexes of the cell - is essential for a better understanding and more global vision of cell function. Using two-dimensional blue native/SDS-PAGE (2-D BN/SDS-PAGE) technology, the cytosolic and membrane protein complexes of Escherichia coli were separated. Then, the different partners of each protein complex were identified by LC-MS/MS. In this report, 306 protein complexes were separated and identified. Among these protein complexes, 50 heteromultimeric and 256 homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(101 citation statements)
references
References 67 publications
3
95
1
Order By: Relevance
“…250 lL of 19 SDS-PAGE loading buffer was added to each cell pellets and vortex until cells were resuspended. Then cells were boiled 5 min in H 2 O bath, the samples were centrifuged at 300 rpm and supernatants were used for 12 % SDS-PAGE study (Lasserre et al 2006). …”
Section: Sds-page Of Whole Cell Proteinsmentioning
confidence: 99%
“…250 lL of 19 SDS-PAGE loading buffer was added to each cell pellets and vortex until cells were resuspended. Then cells were boiled 5 min in H 2 O bath, the samples were centrifuged at 300 rpm and supernatants were used for 12 % SDS-PAGE study (Lasserre et al 2006). …”
Section: Sds-page Of Whole Cell Proteinsmentioning
confidence: 99%
“…In E. coli there was only a limited overlap of 9 integral membrane proteins between the datasets obtained after SDS-TFE-SDS-PAGE and BN-SDS-PAGE separation [5,12,13], indicating that in this organism the approaches are complementary. In yeast mitochondria, only one TFEsensitive protein not integral to the membrane could be identified using our approach.…”
Section: Discussionmentioning
confidence: 99%
“…When applied to E. coli inner membrane preparations, 23 integral membrane proteins and 16 peripheral membrane proteins were identified in off-diagonal spots, while only 14 soluble proteins were found. Comparison to the results of two BN-SDS-PAGE studies on E. coli [12,13], revealed an overlap of only 9 integral membrane proteins and 11 peripheral proteins, indicating that, particularly for integral membrane proteins, the two techniques are complementary. For two of the proteins identified in the SDS-TFE-SDS-PAGE study, the preprotein translocase SecA and the mechanosensitive channel MscS, the oligomeric state and, in the latter case, its dissociation by TFE was confirmed in one dimensional SDS-PAGE gels using immunodetection [8,14].…”
Section: Introductionmentioning
confidence: 99%
“…The agreement between different methods applied to the same genome is not particularly good, although in a favorable case of 31 proteins from the H. pylori type IV secretion system (Terradot et al, 2004) co-purification experiments authenticated 76% of the interactions predicted from large-scale Y2H experiments (Rain et al, 2001). Blue native/SDS-PAGE (sodium dodecyl sulfate polyacrylamide gel electrophoresis) (Wittig and Schagger, 2008) has been used to identify additional protein complexes from H. pylori (Lasserre et al, 2006).…”
Section: Protein Complexes Of Bacteriamentioning
confidence: 99%
“…It has also been shown that proteins that participate in the same interaction share similar mRNA half-lives, a relationship not previously noted (Janga and Babu, 2009). An alternative approach, the use of blue native/SDS-PAGE, followed by the identification of the protein complex by LC-MS/MS, has been used to identify hetero-oligomeric complexes from E. coli (Lasserre et al, 2006). Other studies have focused on characterizing another, although more experimentally challenging set of protein complexes, those found in the membrane (Stenberg et al, 2005).…”
Section: Protein Complexes Of Bacteriamentioning
confidence: 99%